GPR91 deficiency exacerbates allergic contact dermatitis while reducing arthritic disease in mice. Issue 3 (12th September 2016) - Rubić‐Schneider, T.; Carballido‐Perrig, N.; Regairaz, C.; Raad, L.; Jost, S.; Rauld, C.; Christen, B.; Wieczorek, G.; Kreutzer, R.; Dawson, J.; Lametschwandner, G.; Littlewood‐Evans, A.; et al.
Abstract: Background: Succinate, in addition to its role as an intermediary of the citric acid cycle, acts as an alarmin, initiating and propagating danger signals resulting from tissue injury or inflammatory stimuli. The contribution of this immune sensing pathway to the development of allergic and inflammatory responses is unknown. Methods: Ear thickness of wild‐type (wt) and Sucnr1 ‐deficient ( Sucnr1 −/− ) mice, sensitized and challenged with oxazolone, was used as a criterion to assess the relevance of SUCNR1/GPR91 expression mediating allergic contact dermatitis (ACD). Results obtained in this system were contrasted with data generated using passive cutaneous anaphylaxis, ovalbumin‐induced asthma and arthritis models. Results: We found augmented ACD reactions in Sucnr1 −/− mice. This observation correlated with increased mast cell activation in vitro and in vivo . However, exacerbated mast cell activation in Sucnr1 −/− mice did not contribute to the enhancement of asthma or arthritis and seemed to be due to alterations during mast cell development as augmented mast cell responses could be recapitulated in wt mast cells differentiated in the absence of succinate. Conclusions: A deficiency in succinate sensing during mast cell development confers these cells with a hyperactive phenotype. Such a phenomenon does not translate into exacerbation of asthma or mast cell‐dependent arthritis. On the contrary, the fact that Sucnr1 −/− mice developed reduced arthritic disease, using two different in vivo models, indicates that GPR91 antagonists may have therapeutic potential for the treatment of allergic and autoimmune diseases.